When the books and reading friends are up to us: Students’ Responses about an Extensive Reading Program - Evi Puspitasari (Makassar State University, 2020)
Extensive Reading is one of alternatives that help teachers to motivate the students to read. Regarding that main benefit, in one Indonesian university, a teacher established an extensive reading program for freshmen. In the implementation, the teacher allowed the students to choose books and with whom they read. In practice, they made a group of four and met once a week to share what they read. This qualitative research was conducted to investigate students’ responses about the program. By involving six students who joined the program, the data were gained through interviews and reflective essays. The selected participants had different level of English, reading interest, and motives to sign up the program which made the data rich and were able to capture the phenomenon from diverse students’ viewpoints. After the data were obtained, they were coded, categorized to find the themes and interpreted. The result showed, all activities in the program namely choosing own books, having weekly reading in groups, having discussion with their group, and sharing their weekly meeting in their social media got both positive and negative responses. The positive responses appeared from benefits that the participants got while the negative responses came up because of the challenges they faced during the program. All in all, an extensive reading program that accommodates students’ freedom in reading, becomes a successful alternative to cultivate students’ L2 reading motivation if it is implemented by considering some possible encounters.